Comparison of clinical outcomes after transcarotid and transsubclavian versus transfemoral TAVI: a propensity-matched analysis. (25th November 2020) - Villecourt, A; Faroux, L; Muneaux, A; Tassan-Mangina, S; Heroguelle, V; Poncet, A; Nazeyrollas, P; Ruggieri, V.G; Metz, D
Abstract:  : Transcarotid (TC) and transsubclavian (TSc) accesses are increasingly used as alternative approaches for TAVI when the transfemoral (TF) access is not suitable. However, concerns remain about the risk of peri-procedural stroke and long-term outcomes following TC or TSc TAVI. The present study sought to compare early- and long-term outcomes of TC/TSc vs. TF TAVI after propensity-score matching. 260 patients who underwent TAVI through a TF (n=220), TC (n=32) or TSc (n=8) approach at our institution during a 4 years period were identified. A 1:1 matching based on the propensity-score was performed, leading to a population of 40 TF and 40 TC/TSc. Primary endpoints were early complications whereas secondary endpoints were long-term outcomes. There was no difference in the baseline characteristics. At 30-day post-TAVI, there was no difference in mortality and stroke rates between TF and TC/TSc TAVI (5% vs. 5% mortality, p=1.0 and 2 vs. 1 stroke, p=1.0). After a median follow-up of 21 months, the risk of death (p=0.950), stroke (p=0.817) and myocardial infarction (p=0.155) did not differ between the 2 groups. After propensity-score matching, no significant difference in early and long-term outcomes was observed between TF and TSc/TSc TAVI. These findings should encourage Heart-Teams to consider a TC or TSc approach when TF access is not available. Funding Acknowledgement: Type of funding source: None